Making a Difference: Student Perceptions of E-learning Blended with Traditional Teaching Methods - McMahon, Graham; Yeo, Shelley; Williams, Michael (International Journal on E-Learning (IJEL) Corporate, Government, Healthcare, & Higher Education, 2011)
E-learning resources are often used to supplement traditional teaching within tertiary courses, a concept referred to as blended learning. This research examines the effectiveness of blended learning from the students’ perspective. Data were gathered from student surveys and databases to determine if there were correlations between aspects of the teaching units and the degree to which the units utilise blended learning. The results indicate that blended learning has a positive effect on the students’ perceptions of their assessment tasks and learning experiences. Students do not perceive that blended learning has increased their workload and they do not perceive that there has been a change in the quality of teaching.